A REVIEW OF THE INFLUENCE OF VALUE AND ETHICAL LITERACY ON THE FORMATION OF STUDENTS' MORAL CHARACTER IN INDONESIAN SCHOOLS - Akmal Khairani; Naysha Aulia (SocioSphere: Interdisciplinary Journal of Social Sciences and Humanities, 2025)
The formation of students' moral character is a central focus of educational discourse in Indonesia. This systematic literature review examines the influence of value and ethical literacy on shaping students' moral character in Indonesian schools. Value literacy encompasses the comprehension and application of moral principles in daily life, while ethics involves ethical reasoning and decision-making guided by these principles. Employing a qualitative approach, the study investigates 14 studies The study delves into the role of educational systems and curricula, revealing the intricate interplay between policy frameworks, teacher training, and parental involvement in fostering ethical understanding. Results reveal that integrating value literacy and ethics education significantly enhances students' moral awareness and behavior. Schools emphasizing values education through explicit curricula and supportive pedagogy foster environments conducive to moral development. Moreover, teacher roles and parental involvement emerge as pivotal in strengthening moral values and ethical behavior. These findings underscore the need for robust policy interventions and targeted strategies to ensure the long-term effectiveness of moral education practices.